Conjunctive Application of Organic and Inorganic Fertilizers to Improve Soil Fertility and Wheat (Triticum aestivum L.) Productivity in Semi-arid Region - Meena, Narendar Kumar; Latare, A.M.; Singh, M.K.; Sharma, Prashant; Verma, Kamlesh (Annals of Arid Zone, 2022)
Intensive cultivation and use of high-yielding cultivars with the elevated and alone application of inorganic fertilizers cause a severe decline in soil fertility. However, application of organic manure, especially the farmyard manure (FYM), vermicompost (VC), and fly ash (waste of coal-based thermal power plants) along with inorganic fertilizer can be an effective integrated nutrient management technique to sustain the crop productivity. In the view of above facts, a pot experiment was carried out in a completely randomized block design to analyze the influence of the FYM (10, 15, 20 t ha-1), VC (2.5, 5, 7.5 t ha-1), and fly ash (10, 20, 30 t ha-1) along with the recommended dose of fertilizer control (RDF) on the performance of wheat crop and soil physico-chemical properties. The results reveal that the application of RDF + 7.5 t ha-1 VC recorded the maximum plant height (60 days after sowing) (65.3 cm), grain (17.5 g plot-1) and straw yield (19 g plot-1), available N (154.7 kg ha-1) and available S (7.56 mg kg-1) in soil. Whereas, the maximum K (1.623%) and S (0.363%) content in wheat and available K (377.1 kg ha-1) in soil, were recorded with treatment RDF + 20 t ha-1 FYM. The application of the RDF + 5 t ha-1 VC enhanced the available P in the soil. However, conjunctive application of fertilizer did not significantly affect the plant height at 30 days after sowing, effective tiller plot-1, harvest index, P content in wheat straw, bulk density, pH, electric conductivity and organic carbon.